2019
DOI: 10.1002/jat.3825
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin induces mitochondrial dysfunction and cell apoptosis in HepG2 cells via inhibition of the Nrf2 pathway

Abstract: Atorvastatin (ATO) is a 3‐hydroxy‐3‐methylglutaryl‐CoA reductase inhibitor widely used to treat hypercholesterolemia. However, clinical application is limited by potential hepatotoxicity. Nuclear factor‐erythroid 2‐related factor 2 (Nrf2) is a master regulator of cellular antioxidants, and oxidative stress is implicated in statin‐induced liver injury. This study investigated mechanisms of ATO‐induced hepatotoxicity and potential mitigation by Nrf2 signaling. ATO reduced Nrf2 and antioxidant enzyme superoxide d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Apoptosis plays an important role in the study of hepatotoxicity [31,32]. Li et al [33] found that ATO induced mitochondrial dysfunction and apoptosis in hepatoma cells by inhibiting the Nrf2 pathway. Previously, Zhang et al [34] revealed that AS IV, a potential neuroprotective agent, inhibited apoptosis in oxygen-glucose-deprived/re-oxygenated HT22 cells by balancing Bcl-2 and Bax expression.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis plays an important role in the study of hepatotoxicity [31,32]. Li et al [33] found that ATO induced mitochondrial dysfunction and apoptosis in hepatoma cells by inhibiting the Nrf2 pathway. Previously, Zhang et al [34] revealed that AS IV, a potential neuroprotective agent, inhibited apoptosis in oxygen-glucose-deprived/re-oxygenated HT22 cells by balancing Bcl-2 and Bax expression.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, mitochondrial dysfunction is largely associated with the occurrence and development of cancers, aging, as well as age-related neurodegenerative diseases and metabolic syndrome [25]. Meanwhile, it has been shown that the destructive mitochondria, reduced mitochondrial membrane potential (Δψ m ) can be lead by the increased levels of ROS, and ultimately cause apoptosis [26,27]. In this study, NCTD-treated cells showed a significantly decreased Δψ m and an increased ROS production, suggesting that NCTD can lead to mitochondrial dysfunction and subsequently induce apoptosis in MDA-MB-231 cells.…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro study by Wang et al [ 17 ] reported that a combination of atorvastatin and caffeine suppressed proliferation and induced apoptotic death in prostate cancer cells. Li et al [ 18 ] found that atorvastatin induced mitochondrial dysfunction and apoptosis in HepG2 cells. Finally, an in vitro study [ 19 ] showed that atorvastatin reduced aldosterone-induced vascular damage by inhibiting oxidative stress and inflammation in cultured chondrocytes.…”
Section: Discussionmentioning
confidence: 99%